CYBERSECURITY CHALLENGES AND SOLUTIONS IN BLOCKCHAIN-BASED IOT SYSTEMS - Djurayev , Musurmon Avlakulovich; Tuyboyov , Oybek Valijonovich; Salimov, Sirojiddin; Zarifova , Zumrad (Innovative Development in Educational Activities, 2023)
The pervasive integration of the Internet of Things (IoT) is evident across diverse domains, including smart homes, cities, industrial automation, and healthcare. Nonetheless, the escalating utilization of IoT devices has given rise to notable apprehensions regarding cybersecurity and privacy. An emerging proposition to address these concerns involves leveraging blockchain technology, known for its distributed and immutable ledger characteristics, to fortify the security and privacy aspects of IoT systems. Blockchain-infused IoT systems present advantages like decentralization, transparency, and data integrity. Nevertheless, their implementation introduces distinctive cybersecurity challenges that necessitate comprehensive consideration to ensure secure and dependable deployment. This paper undertakes a thorough examination of existing literature, shedding light on the principal cybersecurity challenges associated with blockchain-based IoT systems.